(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article presents geometric research tasks in the formation of functional literacy of students. The role of educational and research activities in the formation of the considered literacy is considered. The main didactic functions of educational research in geometry are shown: the function of discovering new knowledge; the function of deepening the studied knowledge; the function of systematizing the studied knowledge; the function of developing a student, turning him from an object of learning into a subject of self-education. It is also said here that the educational and research work of students is one of the progressive forms of education in a modern school and it allows them to fully identify and develop both their intellectual and potential creative abilities, develops independence skills, research abilities, and forms creative ways of development.